Dare to invest: creative mind and innovative idea / Nik Fazlin Hiryati Nik Jaafar ... [et al.] - Nik Jaafar, Nik Fazlin Hiryati; Ibrahim, Norlaila; Ismail, Rusnah; Wan Chek, Wan Ahmad Khusairi (Universiti Teknologi MARA, Kedah, 2019)
This innovation intends to provide a unique way to inculcate a sense of creative mind and ability to produce innovative ideas among student. It focuses on active learning participation from students with guidance from the facilitator (lecturer). This innovation delivers more structured and designed way of learning method with a combination of few scopes that are entrepreneurship, creativity and innovation. This learning method is categorized as an ‘event’ organized to enhance students’ various skills. The event is divided into four (4) specific slots namely 1) Brainwave 2) Sketch Out Your Idea 3) Showcase Your Creative Mind and lastly 4) Dare to Invest. Uniquely, each of this slot sets to measure different set of skills since they have their own features of implementation. Among the skills measured are; ability to search for relevant information, creative problem solving skill, risk analysis skill, thinking out of box, persuasive skills and many more. The involvement of facilitator is also part of the way to improve students’ communication and cooperation skills. This also allows the facilitator to be able to deliver knowledge and lesson using different ways. In addition to that, this innovation is created with easy-to-follow instruction so that it can be extensively implemented at all level of participation be it school or university student.